Desain Perancangan Alat Holder Nozzle Pemadam Kebakaran dengan Metode QFD untuk Menurunkan Resiko Kerja - Mindar Agus Prasetyo; Annas Affandi; M. Sagaf; Sukarno Budi Utomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
PT ABC is a fuel distribution company operating 24 hours a day, including product receiving and storage activities in tanks across three shifts. A past fire incident at the company highlighted the importance of reliable firefighting equipment. As a solution, a holder nozzle was developed, designed to maintain the nozzle's balance within the firefighting system. This research aims to reduce the ergonomic risks for firefighters and evaluate the effectiveness of the holder nozzle design. The method used involves ergonomic analysis of the nozzle's use during firefighting operations with the cooling technique. The holder nozzle is made of mild steel (Mild Steel/MS), consisting of three main components: a stand hydrant, a pipe stand, and a shaft. Additionally, a flexible joint was added to the discharge pipe to reduce vibration transmission. The results show that the holder nozzle successfully improved firefighting performance by reducing response time, expanding coverage area, and decreasing firefighters' physical fatigue. The implementation of the flexible joint also proved effective in reducing equipment damage risks caused by vibration.